A mother's secret - Meyer, Gabrielle (Love inspired., 2020)
Joy Gordon<U+2019>s life is far from perfect. The lavish house she lives in with her children was loaned to her by a wealthy philanthropist<U+2014>and his death means she has to give up her home. To satisfy his controlling father, Chase Asher must take his great-uncle<U+2019>s property from the woman he once loved<U+2026>but what will he do when he learns he fathered Joy<U+2019>s twins?